2005
DOI: 10.1002/cbic.200500205
|View full text |Cite
|
Sign up to set email alerts
|

LanV, a Bifunctional Enzyme: Aromatase and Ketoreductase during Landomycin A Biosynthesis

Abstract: LanV is involved in the biosynthesis of landomycin A. The exact function of this enzyme was elucidated with combinatorial biosynthesis by using Streptomyces fradiae mutants that produce urdamycin A. After expression of lanV in S. fradiae DeltaurdM, which is a mutant that accumulates rabelomycin, urdamycinon B and urdamycin B were found to be produced by the strain. This result indicates that LanV is involved in the 6-ketoreduction of the angucycline core, which preceeds a 5,6-dehydration reaction. 9-C-D-Olivos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…9 We found that when this strain was fermented using modified-RA medium and the extract was analyzed by HPLC-DAD-UV, an array of secondary metabolites with UV spectra characteristic of the angucycline class of antibiotics was observed. 10,11 In this paper, we report the fermentation, isolation, and structure elucidation of five new angucycline C-glycosides, grincamycins B−F (1−5), from S. lusitanus SCSIO LR32 along with the previously reported grincamycin (6). Moreover, we report the cytotoxicities of compounds 1−6 against the human cancer cell lines HepG2, SW-1990, HeLa, NCI-H460, and MCF-7 and the mouse melanoma cell line B16.…”
mentioning
confidence: 86%
“…9 We found that when this strain was fermented using modified-RA medium and the extract was analyzed by HPLC-DAD-UV, an array of secondary metabolites with UV spectra characteristic of the angucycline class of antibiotics was observed. 10,11 In this paper, we report the fermentation, isolation, and structure elucidation of five new angucycline C-glycosides, grincamycins B−F (1−5), from S. lusitanus SCSIO LR32 along with the previously reported grincamycin (6). Moreover, we report the cytotoxicities of compounds 1−6 against the human cancer cell lines HepG2, SW-1990, HeLa, NCI-H460, and MCF-7 and the mouse melanoma cell line B16.…”
mentioning
confidence: 86%
“…The hrbI gene resembles lanV, a 6-ketoreductase gene in landomycin biosynthesis (12), and is assignable to the same function (Fig. 5).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, enzymes that employ such "substrate-assisted" catalysis have been characterised from other aromatic poly-A C H T U N G T R E N N U N G ketide biosynthesis pathways. [17,46,47] Moreover, unusual bifunctionality has been observed with enzymes that catalyse angucycline post-PKS reactions, [21,22] supporting the high inherent reactivity of the substrates. Finally, the lack of sequence-tofunction correlation with angucycline monooxygenases indicates that their function cannot be deduced in silico and suggests that gene products from the other unknown clusters (AlpF and Aur1I) might encode novel activities.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore it is likely that CabV and the reductase domain of PgaM catalyse 2,3-dehydration in a manner similar to that seen in landomycin biosynthesis, where it has been suggested that aromatisation of the A-ring occurs through the action of a homologous reductase lanV. [21] According to sequence analyses the angucycline reductases are most closely related to SDR dehydrogenases. [43,44] However, the so called "extended SDR superfamily" does contain members that use the same conserved tyrosine residue in the active site for dehydration reactions, [43,45] which gives support to the 2,3-dehydration function assigned here.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation